25 years of food policy research: reflections by Per Pinstrup-Andersen - Pinstrup-Andersen, Per (International Food Policy Research Institute, 2000)
On the occasion of IFPRI's 25th anniversary, the author has selected a few subjects where the Institute has made an important and recognized contribution to food policy research, either by itself or, more frequently, with others. In each case the topic has broad application and the research includes innovative conclusions or methodology. This has necessarily meant looking more to the past than the present, although in many cases the work is continuing and promises a good deal more, in addition to what has already been achieved. He addresses IFPRI's accomplishments and the influence it has had on the development community’s views on policy issues and the nature of development in general. These areas are discussed: Global Food Trends, Food Subsidies, Markets under Structural Adjustment, Agricultural Linkages, The Bias Against Agriculture, Household Food Security, The Environment, Agricultural Science and Technology Policy, Building Food Policy Research Capacity, Trade and Globalization, and The 2020 Vision Food, Agriculture, and the Environment Initiative, through which IFPRI seeks to refocus attention on current and future challenges in areas such as food security, agricultural development, rural poverty, and environmental protection.